2001
DOI: 10.1177/108705470100400401
|View full text |Cite
|
Sign up to set email alerts
|

Visual selective attention versus sustained attention in boys with Attention-Deficit/ Hyperactivity Disorder

Abstract: This study examined selective attention and sustained attention in children with ADHD. Performance of 10-year-old boys on a visual cueing task was examined as a measure of selective attention. A subset of the original participants returned for a second study, during which they completed the Conners' Continuous Performance Test (CPT) as a measure of sustained attention. The results of this investigation suggest a dissociation between selective and sustained attention abilities in children with ADHD. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
(46 reference statements)
2
9
1
Order By: Relevance
“…Thus, the CCPT-II did not demonstrate sensitivity to ADHD, as it failed to differentiate individuals with ADHD from normal, nonclinical controls. This finding is inconsistent with previous results reported by DeShazo et al (2001), Perugini et al (2000, and Walker et al (2000). However, these results are congruent with findings that have shown that the CCPT is not sensitive to the effects o f ADHD when the comparison group was a clinical control group (Katz et al, 1998;Kovner et al, 1998;McGee et al, 2000).…”
Section: The Ccpt-iicontrasting
confidence: 93%
“…Thus, the CCPT-II did not demonstrate sensitivity to ADHD, as it failed to differentiate individuals with ADHD from normal, nonclinical controls. This finding is inconsistent with previous results reported by DeShazo et al (2001), Perugini et al (2000, and Walker et al (2000). However, these results are congruent with findings that have shown that the CCPT is not sensitive to the effects o f ADHD when the comparison group was a clinical control group (Katz et al, 1998;Kovner et al, 1998;McGee et al, 2000).…”
Section: The Ccpt-iicontrasting
confidence: 93%
“…This study should involve many time points and verify the genes involved in predicting risk and the eventual development of inattentive symptoms. Although it is unclear how reflexive attention and sustained attention are related (Hikosaka et al, 1993; Suzuki and Cavanagh, 1997; Barry et al, 2001; Berger et al, 2005; Andrade et al, 2009; Henderickx et al, 2010; Carrasco, 2011; Macaluso and Doricchi, 2013; Underbjerg et al, 2013; Dye and Hauser, 2014; Anderson, 2015), my previous work has indicated that reflexive attention is related to day-to-day attentional performance (Lundwall, 2013). Second, in conjunction with the above, several comparison intervention programs could be targeted earlier to determine which are most effective.…”
Section: Discussionmentioning
confidence: 99%
“…It can be contrasted to sustained attention, the other component of attention. Some studies suggest that reflexive and sustained attention are independent components of overall attention (Barry et al, 2001; Berger et al, 2005; Andrade et al, 2009; Underbjerg et al, 2013; Dye and Hauser, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…However, many aspects of this disorder are still not well understood. For example, impairments in sustained attention and inhibition are thought to be primary deficits of the disorder [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it allows for examination of three different aspects of visual selective attention (preparatory facilitation, preparatory suppression, and stimulus suppression) that have not been examined in this population. Understanding these different aspects of selective attention may help to explain how it is possible that those with ADHD are able to compensate behaviorally in visual selective attention tasks [3] as well as to help understand ADHD more completely. It may also provide additional evidence in support of this four-component model of selective attention (i.e.…”
Section: Introductionmentioning
confidence: 99%